2021
DOI: 10.1002/hup.2790
|View full text |Cite
|
Sign up to set email alerts
|

The type 2 diabetes mellitus susceptibility gene CDKAL1 polymorphism is associated with depressive symptom in first‐episode drug‐naive schizophrenic patients

Abstract: Background: Patients with schizophrenia have an increased prevalence of type 2 diabetes mellitus that has shown a significant association with the rs7754840 polymorphism in the gene encoding the cyclin-dependent kinase 5 (CDK5) regulatory subunit-associated protein 1-like 1 (CDKAL1).Objective: To examine whether this polymorphism was involved in the susceptibility in first-episode drug-naive schizophrenic patients (FDSP), and further influenced their clinical symptoms.Methods: This polymorphism was genotyped i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Psychiatric symptoms in patients were assessed by the Chinese Version of the Positive and Negative Syndrome Scale (PANSS) ( 23 ). A previous study has reported a new PANSS five-factor model including positive symptoms (composed of four PANSS items: P1, P3, P6, and G9), negative symptoms (composed of six PANSS items: N1, N2, N3, N4, N6, and G7), cognitive symptoms (composed of three PANSS items: P2, N5, and G11), excited symptoms (composed of four PANSS items: P4, P7, G8, and G14), and depressive symptoms (composed of three PANSS items: G2, G3, and G6) ( 24 , 25 ). The use of the Chinese version of PANSS was simultaneously trained for the attending psychiatrists prior to the initiation of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Psychiatric symptoms in patients were assessed by the Chinese Version of the Positive and Negative Syndrome Scale (PANSS) ( 23 ). A previous study has reported a new PANSS five-factor model including positive symptoms (composed of four PANSS items: P1, P3, P6, and G9), negative symptoms (composed of six PANSS items: N1, N2, N3, N4, N6, and G7), cognitive symptoms (composed of three PANSS items: P2, N5, and G11), excited symptoms (composed of four PANSS items: P4, P7, G8, and G14), and depressive symptoms (composed of three PANSS items: G2, G3, and G6) ( 24 , 25 ). The use of the Chinese version of PANSS was simultaneously trained for the attending psychiatrists prior to the initiation of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Previous family-based genomewide linkage studies identified a number of overlapping risk loci between schizophrenia and diabetes, including chromosomes 1p13, 1p36, 1q21-24, 1q25, 2p13-22, 2q14, 2q33, 2q36, 3p22, 3q29, 4q25, 5q13, 6p21, 6q25, 7p15, 7p21, 7q21, 7q31, and 9p24 [154,155], which are the gene-rich regions that harbor multiple common candidate genes for susceptibility to these disorders [156]. Possible pleiotropic genes identified for targeting the association with metabolic syndrome susceptibility in persons with schizophrenia include the catechol-O-methyltransferase gene (COMT), endocannabinoid receptor type 1 gene (CNR1), brain-derived neurotrophic factor gene (BDNF), methylenetetrahydrofolate reductase gene (MTHFR), serotonin receptor 2A gene (HTR2A), serotonin receptor 2C gene (HTR2C), fat mass and obesity-associated gene (FTO), leptin gene (LEP), leptin receptor gene (LEPR) [157], cyclin-dependent kinase 5 regulatory subunit-associated protein 1-like 1 gene (CDKAL1) [158], nitric oxide synthase 3 gene (NOS3) [159], solute carrier family 2 member 2 gene (SLC2A2), forkhead box O3 gene (FOXO3), and furin gene (FURIN) [160].…”
Section: Co-shared Genetics Pathway In Schizophrenia and Metabolic Sy...mentioning
confidence: 99%